Pengaruh Suku Bunga dan Tingkat Inflasi terhadap Kinerja Keuangan pada Industri Perbankan yang Terdaftar di Bursa Efek Indonesia (BEI) - Syafi’i A. Basalamah, Muhammad; Fadhilah, Resky Nur; Sinring, Bahar (Jurnal Mirai Management, 2024)
This research aims to: (1) analyze the influence of interest rates on the financial performance of the banking industry listed on the IDX during the period of 2018-2022; (2) analyze the influence of inflation rates on the financial performance of banking industry listed on the IDX during the period of 2018-2022. This research utilizes preprocessed data, namely data obtained by the researcher from written sources commonly referred to as secondary data such as books, journals, or other documents related to the writing of the research. In this study, the annual reports of banking companies listed on the Indonesia Stock Exchange are also a primary focus. The data is analyzed using the Statistical Product and Service Solutions (SPSS) program. The results of this study indicate that: (1) Interest rates have a significant negative influence on the financial performance of banking industry listed on the Indonesia Stock Exchange (IDX) during the period of 2018-2022; (2) Inflation rates have a significant negative influence on the financial performance of banking industry listed on the Indonesia Stock Exchange (IDX) during the period of 2018-2022. This means that the higher the interest rates applied by companies in the banking industry, the lower the financial performance generated. However, when the interest rates applied by companies in the banking industry are stable or not too low, it may lead to an increase in the resulting financial performance. On the other hand, the higher the perceived inflation rate by companies in the banking industry, the lower the financial performance generated. However, when the perceived inflation rate by companies in the banking industry is stable or not too low, it may lead to an increase in the resulting financial performance.. Keywords: Interest rates, Inflation rate, Financial Performance, Banking.